Clube Português do Pâncreas Recommendations for Chronic Pancreatitis: Etiology, Natural History, and Diagnosis (Part I) - Rodrigues-Pinto, Eduardo (2019)
Chronic pancreatitis (CP) is a heterogeneous disease, with different causes and often a long delay between onset and full classic presentation. Clinical presentation depends on the stage of the disease. In earlier stages, recurrent episodes of acute pancreatitis are the major signs dominating clinical presentation. As the inflammatory process goes on, less acute episodes occur, and pain adopts different aspects or may even disappear. After 10-15 years from onset, functional insufficiency occurs. Then, a classic presentation with pain and pancreatic exocrine and endocrine insufficiency appears. Diagnosis remains challenging in the early stages of the disease, as its initial presentation is usually ill-defined and overlaps with other digestive disorders. Computed tomography and magnetic resonance cholangiopancreatography should be the first choice in patients with suspected CP. If the results are normal or equivocal but still there is a high suspicion of CP, the next option should be endoscopic ultrasound. Endoscopic retrograde cholangiopancreatography is mainly a therapeutic technique, and for the diagnostic purpose should only be used when all other imaging modalities and pancreatic function tests have been exhausted. Indirect tests are used to quantify the degree of insufficiency in already-established late CP. Recommendations on CP were developed by Clube Português do Pâncreas (CPP), based on literature review to answer predefined topics, subsequently discussed and approved by all members of CPP. Recommendations are separated in two parts: "chronic pancreatitis etiology, natural history, and diagnosis," and "chronic pancreatitis medical, endoscopic, and surgical treatment." This abstract pertains to part I.